A Case of Malignant Pheochromocytoma Detected during Fertility Treatment - Kazuhisa Hagiwara; Itsuto Hamano; Ayumu Kusaka; Hiromi Murasawa; Noriko Tokui; Kengo Imanishi; Akiko Okamoto; Hayato Yamamoto; Atsushi Imai; Shingo Hatakeyama; Takahiro Yoneyama; Yasuhiro Hashimoto; et al. (Case Reports in Urology)
We report a case of malignant pheochromocytoma in a 35-year-old Japanese woman during fertility treatment, successfully treated with surgical excision. The patient recovered without any postoperative problems, and plasma catecholamine levels normalized. At present, 18 months after the operation, there are no signs of relapse.